2013
DOI: 10.1128/jvi.01435-13
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Regulatory Factor 4 Is Activated through c-Src-Mediated Tyrosine Phosphorylation in Virus-Transformed Cells

Abstract: Interferon regulatory factors (IRFs) are a small but important family of transcription factors in multiple facets of host defense systems and are also involved in the regulation of tumorigenesis, cell growth, differentiation, and myeloid cell development (1). Among IRFs, IRF2 (2), -4 (3), and -7 (4) have oncogenic and transforming potentials and antiapoptotic activity (3,5,6). These oncogenic IRFs all intimately interact with Epstein-Barr virus (EBV) latency programs (3, 7-10), which are associated with a vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…37 We have previously provided strong evidence that c-Src activates IRF4, and Src(Y418) is phosphorylated and therefore Src is active, in EBV-transformed cells. 36 We have also shown that the total endogenous Src protein levels and activity correlate with the LMP1 protein levels in EBV latency. 36 These observations suggest that, in EBV latency, LMP1 can stimulate Src activation, which then leads to IRF4 phosphorylation.…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…37 We have previously provided strong evidence that c-Src activates IRF4, and Src(Y418) is phosphorylated and therefore Src is active, in EBV-transformed cells. 36 We have also shown that the total endogenous Src protein levels and activity correlate with the LMP1 protein levels in EBV latency. 36 These observations suggest that, in EBV latency, LMP1 can stimulate Src activation, which then leads to IRF4 phosphorylation.…”
Section: Resultsmentioning
confidence: 60%
“…We also used the IRF4 mutant, IRF4(Y121/124F) that is deficient in response to Src, 36 to test its ability to respond to LMP1. As shown in Figure 1d, activation of IRF4(Y121/124F) by LMP1 is significantly impaired, compared with wild-type IRF4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, EBV transformed lymphoblastoid cell lines showed reduced proliferation and enhanced apoptosis upon IRF4 knock-down (Banerjee et al, 2013). IRF4 was further shown to be phosphorylated in a c-src dependent manner which interfered with the DNA binding ability of IRF4 in EBV transformed cells (Wang and Ning, 2013). Furthermore, EBNA3C was shown to bind AICE and EICE sites in p14 (ARF)/CDKN2A locus, to repress its expression (Jiang et al, 2014b; Portal et al, 2013).…”
Section: Viral Infections and Associated Malignanciesmentioning
confidence: 99%